2014
DOI: 10.1093/abbs/gmt153
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reference genes for qRT-PCR in human lung squamous-cell carcinoma by RNA-Seq

Abstract: Although the accuracy of quantitative real-time polymerase chain reaction (qRT-PCR) is highly dependent on the reliable reference genes, many commonly used reference genes are not stably expressed and as such are not suitable for quantification and normalization of qRT-PCR data. The aim of this study was to identify novel reliable reference genes in lung squamous-cell carcinoma. We used RNA sequencing (RNA-Seq) to survey the whole genome expression in 5 lung normal samples and 44 lung squamous-cell carcinoma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 53 publications
(35 reference statements)
0
42
0
Order By: Relevance
“…39 43 44 In one study, PGK1 and PPIA (Peptidyl-prolyl cis-trans isomerase A) were undetectable by RNA-Seq in human lung squamous cell carcinoma, and so were deemed inappropriate for use as reference genes. 45 The differences between these observations and ours may be explained by the analogous comparison to the difference between human and mouse samples, as well as the difference between analyses in cell line and primary tissues. Indeed, several studies have shown that the selection of the most appropriate reference gene in cancer tissue is dependent on the specific nature of the experiment.…”
Section: Discussionmentioning
confidence: 56%
“…39 43 44 In one study, PGK1 and PPIA (Peptidyl-prolyl cis-trans isomerase A) were undetectable by RNA-Seq in human lung squamous cell carcinoma, and so were deemed inappropriate for use as reference genes. 45 The differences between these observations and ours may be explained by the analogous comparison to the difference between human and mouse samples, as well as the difference between analyses in cell line and primary tissues. Indeed, several studies have shown that the selection of the most appropriate reference gene in cancer tissue is dependent on the specific nature of the experiment.…”
Section: Discussionmentioning
confidence: 56%
“…In RT-PCR or qRT-PCR, the expression of a target gene is normalized to the expression of a putatively stably expressed reference gene (Vandesompele et al 2002). In practice, the stability of expression for a potential reference gene is assessed by comparison to other genes (Vandesompele et al 2002) or based on expression profiles from microarrays (Libault et al 2008;Cheng et al 2011) or RNA-Seq (Zhan et al 2014). In other words, reference genes are selected whose expression is assumed to comprise a constant fraction of the transcriptome.…”
Section: Measuring Gene Expression: What Do (And Don't) Standard Methmentioning
confidence: 99%
“…Each sample was measured in triplicate and a negative control was included with every RT-qPCR assay. β-actin was used as the reference gene instead of GAPDH since a recent study reported that the latter had differential expression between LSCC and NT samples [42]. Relative expression levels were quantified based on the crossing point values and normalized to the reference gene.…”
Section: Methodsmentioning
confidence: 99%